2017
DOI: 10.1590/0037-8682-0315-2016
|View full text |Cite
|
Sign up to set email alerts
|

Serosurvey of anti- Leptospira sp. and anti- Toxoplasma gondii antibodies in capybaras and collared and white-lipped peccaries

Abstract: Introduction: Brazilian native species are reemerging as increasingly free-ranging populations. Methods: Sera from 31 capybaras (Hydrochoerus hydrochaeris) and 28 peccaries (Pecari tajacu and Tayassu pecari) were tested for anti-Leptospira and anti-Toxoplasma gondii antibodies using microscopic seroagglutination test. Results: Nineteen percent of free-ranging and 10.0% of captive capybaras, along with 31.8% of collared peccaries, were seropositive for T. gondii. None was seropositive for Leptospira sp. Conclus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 14 publications
0
5
1
Order By: Relevance
“…The individuals surveyed here reported that they hunted small, medium, and large wild animals, including native capybaras and exotic invasive species such as wild boars. In studies on T. gondii seropositivity among capybaras, although 16/26 healthy free-range capybaras (61.5%) caught in a large nearby city, 160 km (100 miles) from the present study, were seropositive [36], another study within the same state of Paraná found seropositivity in only 4/21 free-range capybaras (16.1%) and 1/10 captive capybaras in a zoo (10.0%) [37].…”
Section: Discussioncontrasting
confidence: 71%
See 1 more Smart Citation
“…The individuals surveyed here reported that they hunted small, medium, and large wild animals, including native capybaras and exotic invasive species such as wild boars. In studies on T. gondii seropositivity among capybaras, although 16/26 healthy free-range capybaras (61.5%) caught in a large nearby city, 160 km (100 miles) from the present study, were seropositive [36], another study within the same state of Paraná found seropositivity in only 4/21 free-range capybaras (16.1%) and 1/10 captive capybaras in a zoo (10.0%) [37].…”
Section: Discussioncontrasting
confidence: 71%
“…While a study in the state of Paraná showed seropositivity for T. gondii in 7/22 collared peccaries (31.8%) and in 0/6 white-lipped peccaries (0%) that were kept in captivity [ 37 ], a study conducted in Peru found that 90/101 white-lipped peccaries (89.1%) that had contact with domestic animals were seropositive [ 40 ]. Furthermore, infective T. gondii was isolated from black-eared opossums living in an urban area in southeastern Brazil [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among wildlife species used for hunting, seroprevalence on native Brazilian species revealed T . gondii seropositivity in 4/21 (19.0%) of free-range and 1/10 (10.0%) captive capybaras, along with 7/22 (31.8%) captive collared peccaries [23]. Furthermore, Brazilian rural areas have higher human and domestic animal seroprevalence of T .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Leptospira environmental survival may be favored by multispecies natural biofilm formation and protection, with virulent Leptospira interactions with complex environmental microbiota [ 6 ]. Regardless, Leptospira infection mostly occurs through the urine of infected rats [ 9 ] and other domestic [ 10 ] and wild [ 11 ] animals, favored in tropical regions [ 1 ] due to exposure to contaminated flooding water [ 9 ]. As human cases generally occur after heavy rain, rainfall water may resuspend and spread leptospires together with soil particles to infect humans or animals through body wounds in the skin, mucous membranes and conjunctiva [ 6 ].…”
Section: Introductionmentioning
confidence: 99%